(untitled) (Per Musi, 2018)
The purpose of this article is to apply some features of the theory of contour, by Morris (1987), on the melodic reduction of a so-called street frevo, which is a musical genre from Pernambuco, Brazil. It also considers its pitch class order, timbric diversity, and other musical elements, such as horizontal gestures, form, number of bars, and sections. All these features are applied on a piece composed for a brass quintet. The rhythmic events are identified by a list of elements observed in a song composed by the first author of this article and also in other five songs by Inaldo Moreira, a Brazilian composer. Based on Joseph Straus’s revisionary ratios (STRAUS, 1990), known as marginalization, such rhythmic cells are disposed according to how often they appear in the analyzed songs. Finally, the rhythmic tapping is used so that the link between contemporary language and street frevo takes place. It concludes that such methodology provides enough support for a composing process.